2017
DOI: 10.1186/s12891-017-1510-8
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue strength of bovine articular cartilage-on-bone under three-point bending: the effect of loading frequency

Abstract: BackgroundThe objective of this study was to determine the influence of loading frequency on the failure of articular cartilage-on-bone specimens under three-point bending.MethodsIn this study, cyclic three-point bending was used to introduce failure into cartilage-on-bone specimens at varying loading frequencies. Sinusiodally varying maximum compressive loads in the range 40–130 N were applied to beam-shaped cartilage-on-bone specimens at frequencies of 1, 10, 50 and 100 Hz.ResultsThe number of cycles to fail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 56 publications
1
17
0
Order By: Relevance
“…However, our finding is consistent with studies which have measured: increased dynamic moduli with increased induced stress derived from the slope of the stress strain curves ( Park et al, 2004 ); and, the moduli of articular cartilage to approximate that of the underlying cancellous bone during impact loading ( Burgin and Aspden, 2008 ). All of which is consistent with the proposition that cartilage undergoes a glass transition, so that at higher rates of loading, and/or higher frequencies, it becomes more rigid ( Fulcher et al, 2009 ) but also more prone to failure ( Sadeghi et al, 2017a , Sadeghi et al, 2017b ; Sadeghi et al, 2015b ).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…However, our finding is consistent with studies which have measured: increased dynamic moduli with increased induced stress derived from the slope of the stress strain curves ( Park et al, 2004 ); and, the moduli of articular cartilage to approximate that of the underlying cancellous bone during impact loading ( Burgin and Aspden, 2008 ). All of which is consistent with the proposition that cartilage undergoes a glass transition, so that at higher rates of loading, and/or higher frequencies, it becomes more rigid ( Fulcher et al, 2009 ) but also more prone to failure ( Sadeghi et al, 2017a , Sadeghi et al, 2017b ; Sadeghi et al, 2015b ).…”
Section: Discussionsupporting
confidence: 86%
“…This is not surprising as energy from potentially damaging loading, off-bone, might be dissipated via increased hysteresis; however, on-bone cartilage might dissipate excess energy through the formation of cracks in the cartilage. Clearly, propensity to failure is multi-factorial, dependent on factors including: high induced stresses (which increased the storage/loss ratio by up to 3.5 when compared to walking induced stresses); hydration ( Pearson and Espino, 2013 ); and frequency of loading ( Sadeghi et al, 2017a , Sadeghi et al, 2017b ; Sadeghi et al, 2015b ). Further, while regions with differing matrix integrity across a joint ( Bullough et al, 1985 ) may have a similar storage/loss ratio ( Espino et al, 2014 ), a compromised matrix may well have a lower storage/loss failure threshold (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Sadeghi et al suggested that to date, there is little data on the variation of mechanical properties of bone with increasing loading frequency. 33 Lafferty & Raju reported that for the cortical bone, with increased loading frequencies (from 30 to 125 Hz), the number of cycles required to produce fracture decreases. 22 Another indirect evidence is provided by Burr et al, who measured in vivo strains in the human tibia during walking and running, and reported that the strain experienced by bone was higher for running than walking, some of it is perhaps due to larger forces exerted during running.…”
Section: Resultsmentioning
confidence: 99%
“…The dynamic test followed the arrangement of three point bending fatigue measurements. (21,22). Prior the dynamic tests, the stiffness of each ribs was determined by measuring the force-de ection curve between 0.2 and 0.8 mm de ection.…”
Section: Methodsmentioning
confidence: 99%